Priority themes on active transparency in federal institutions of higher education: A systematic mapping - Souza, Diego Fillipe de; Cavalcanti, Emilly Kessia da Costa; Castro, Marcos Paulo de Assis; Azevedo, Érika Sabrina Felix; Neto, Jorge da Silva Correia (Seven Editora, 2023)
Initiatives aimed at citizen participation, transparency and the use of technologies have led public management to new directions. Open government is an international initiative that encourages governments that are more transparent, accountable and open to social participation. An interesting initiative applied in Brazil is the proactive dissemination of information of collective interest to society by these bodies and entities, including federal institutions of higher education (IFES), due to their social role and potential for disseminating knowledge to society. . In this context, the objective of this work is to identify which are the themes of collective interest in IFES for the due fulfillment of active transparency. For this, a bibliographic survey, a documentary research and a systematic mapping study were carried out, enhancing the results found. As a result, some general and specific themes of collective interest in IFES were identified. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-106